DUKUNGAN SUAMI TERHADAP PERILAKU IBU HAMIL DALAM PEMERIKSAAN ANTENATAL CARE PADA MASA PANDEMI COVID 19 - Tiwatu, Filia V.; Lumintang, Cyntia (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction: Husband's support is the support given by husbands to wives who are pregnant, both physical and psychological comfort. Husband's support will motivate pregnant women to seek good health services and carry out antenatal care (ANC) visits obediently in order to protect the condition of the mother and the fetus in her womb. Objective: The purpose of this study was to determine the relationship between husband's support and pregnant women's behavior in carrying out ANC examinations during the Covid 19 pandemic. Methods: This study used a cross-sectional design with a purposive sampling technique. The population in this study were all pregnant women in the working area of ​​the Modoinding Public Health Center. Results: The results of the study with the Chi-Square test showed a p value of 0.062 (p value <0.05). Conclusion: There is no relationship between husband's support and pregnant women's behavior in carrying out ANC examinations during the Covid 19 pandemic.